2010
DOI: 10.1603/en10035
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Generation Effects of Bt Rice on Anagrus nilaparvatae, a Parasitoid of the Nontarget Pest Nilapavarta lugens

Abstract: Little is known about the potential cumulative long-term effects of transgenic crops on nontarget organisms. In the present laboratory study, the potential cumulative effects of transgenic Bacillus thuringiensis (Bt) rice on parasitoids in successive generations were observed for an egg parasitoid, Anagrus nilaparvatae parasitizing eggs of Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) feeding on Bt rice. Enzyme-linked immunosorbent assay test confirmed that Cry1Ab insecticidal protein could be detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…These results are inconsistent with some studies that reported that natural enemy species can uptake and even bio-accumulate Cry toxins delivered by their prey (Couty et al, 2001;Bernal et al, 2002;Zhang et al, 2006a;Gao et al, 2010;Paula & Andow, 2016), as Cry1Ab concentrations in corresponding aphids were still detectable at low levels. The Cry1Ab concentrations in P. japonica agreed with the results of Cry1Ab concentrations in aphids and feeding amounts for the 5422Bt1 and 5422CBCL treatments.…”
Section: Discussioncontrasting
confidence: 98%
“…These results are inconsistent with some studies that reported that natural enemy species can uptake and even bio-accumulate Cry toxins delivered by their prey (Couty et al, 2001;Bernal et al, 2002;Zhang et al, 2006a;Gao et al, 2010;Paula & Andow, 2016), as Cry1Ab concentrations in corresponding aphids were still detectable at low levels. The Cry1Ab concentrations in P. japonica agreed with the results of Cry1Ab concentrations in aphids and feeding amounts for the 5422Bt1 and 5422CBCL treatments.…”
Section: Discussioncontrasting
confidence: 98%
“…Thus, exposure to Cry toxins in the field has been reported in predators belonging to different taxa, such as Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae), Orius majusculus (Reuter) (Hemiptera: Anthocoridae) or Stethorus punctillum Weise (Coleoptera: Coccinellidae) (Harwood et al ., ; Obrist et al ., ; Álvarez‐Alfageme et al ., ). The exposure of parasitoids to the toxin has been only demonstrated under laboratory conditions in Anagrus nilaparvatae Pang et Wang (Hymenoptera: Mymaridae) when parasitizing eggs of Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) feeding on Bt rice (Gao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In the last 15 years, laboratory studies have demonstrated that some natural enemy species can uptake and even bioaccumulate Cry toxins delivered from their prey (Couty et al 2001;Zhang et al 2006;Gao et al 2010;Paula and Andow 2015). Uptake is the absorption of a chemical from the food (USEPA 2013), i.e.…”
Section: Introductionmentioning
confidence: 99%